Understanding Escalation Through Intimate Partner Homicide Narratives. (December 2022) - Kafonek, Katherine; Gray, Andrew C.; Parker, Karen F.
The study aims to expand our understanding of escalation from intimate partner violence to intimate partner homicide (IPH) by exploring the known circumstances leading up to a lethal event. The study draws on qualitative data from law enforcement reports and coroner/medical examiner reports within the National Violent Death Reporting System to identify themes preceding and surrounding IPH incidents. Findings support the utility of risk assessments in identifying escalation while illustrating the complex ways that violence between current or former intimate partners can escalate to lethality, particularly the role of separation and the use of firearms.